PENGARUH PENYULUHAN MELALUI MEDIA VIDEO TERHADAP PENGETAHUAN WANITA USIA SUBUR TENTANG PEMERIKSAAN PAP SMEAR DI BANJAR KAYUTULANG DESA CANGGU - Ni Made Artini; Ni Made Risna Sumawati; I Gusti Agung Manik Karuniadi; Pande Indah Purnamayanthi (Jurnal Maternitas Kebidanan, 2024)
Cervical cancer begins in the cells that line the cervix at the bottom of the uterus and spreads progressively across a woman's cervix (the entrance to the uterus from the vagina). One of the preventive measures that has been carried out is screening through the Acetic Acid Visual Inspection method and pap smear. Health education can be delivered using a variety of ways and media/tools. One form of conveying messages in communication and providing health education is counseling. The media for conducting counseling uses video media. Video media is one of the practical audio-visual electronic media and is entertaining and suitable for learning with advances in technology. Health education through video media has advantages in terms of providing good visualization to facilitate the process of absorbing knowledge. This research aims to determine the influence of education through video media on the knowledge of women of childbearing age regarding Pap smear examinations. in Banjar Kayutulang, Canggu Village This research uses a quasi-experimental design type of research with nonequivalent control group design research. The sample selection in this research used the Total Sampling Technique. The sample from this research was all WUS as many as 80 people. Data were analyzed using analysis using the Mann-Whitney test The results of the analysis using the Mann-Whitney test from the results of the statistical tests carried out obtained a value of p=0.00 (<0.05) which means Ho is rejected and Ha is accepted and it can be concluded that there is an influence of education via video media on the knowledge of women of childbearing age about pap examinations. smear in Banjar Kayutulang, Canggu Village. Based on the results of this research, it is hoped that women of childbearing age can increase their knowledge about early detection of cervical cancer by doing a Pap Smear examination.